Pengaruh Product Acceptability Dan Attitude Towards Product Placement Terhadap Purchase Intention Produk Scarlett Whitening Pada Penonton Drama Korea Reborn Rich - Zulfa, Chofifah; Rubiyanti, R. Nurafni (eProceedings of Management, 2024)
Developments in the digital era now have a positive impact and can be utilized well. One beauty brand that paysattention to effective marketing is Scarlett Whitening. In the current digitalization era, Scarlett Whitening's marketingstrategy does not only focus on its products, but by combining the online and offline worlds. One of the efforts madeto increase product acceptance of this brand, especially among kdrama lovers, is to implement a product placementprogram on Korean dramas. The purpose of this study was to examine how the influence of Product acceptability andAttitude Towards Product placement on Purchase Intention of Scarlet Whitening products in the audience of theKorean drama Reborn Rich. The research method used is quantitative with a descriptive approach, usingnonprobability sampling techniques with a total of 103 respondents. Data collection was carried out by distributingquestionnaires to consumers who watched the Korean drama Reborn Rich. Data analysis was carried out using theSEM-PLS method with the help of SmartPLS 3.2.9 software. The results of this study indicate that Productacceptability has a positive and significant influence on Purchase Intention in the audience of the Korean DramaReborn Rich. In addition, Attitude Towards Product placement has a positive and significant influence on PurchaseIntention. The findings also show that Product acceptability has a positive and significant influence on purchaseintention mediated by Attitude Towards Product placement on Scarlet Whitening products in the Korean dramaReborn Rich.Keywords-product acceptability, attitude towards product placement, purchase intention